Clear Air Turbulence Observed Across a Tropopause Fold Over the Drake Passage—A Case Study. Issue 4 (17th February 2022) - Rodriguez Imazio, Paola; Dörnbrack, Andreas; Urzua, Rodrigo Delgado; Rivaben, Nicolás; Godoy, Alejandro
Abstract: An aircraft turbulence encounter over the Drake Passage is investigated by combining unique high‐frequency flight level data, vertical profiles of a near‐simultaneous radiosonde profile and numerical results from global and regional numerical weather prediction (NWP) models. Meteorological analysis reveals an intense polar low propagating from the Bellinghausen Sea toward the Drake Passage. A small and deep stratospheric intrusion formed a tropopause fold that promoted strong upper‐level frontogenesis and enhanced shear and horizontal deformation of the upper tropospheric and lower stratospheric (UTLS) airflow. In this region, the Basic HALO Measurement and Sensor System (BAHAMAS) aboard the HALO research aircraft flying at FL450 detected large peak‐to‐peak variations in all meteorological parameters. The computed Energy dissipation rate (EDR) values (cubic root of the eddy dissipation rate) indicate moderate to severe turbulence. The location of this turbulence encounter was well‐predicted by the clear air turbulence (CAT) indices derived from the NWP results. The enhanced CAT indices emphasize the large shear and horizontal deformation of the airflow as the cause of the turbulence. Horizontal and vertical energy spectra calculated from the 10 Hz BAHAMAS data show a well‐defined energy cascade toward small scales with Kolmogorov scaling. Maximum EDR values of about 0.35 derived both from the spectra and structure functions for the wind speed agree quantitatively very well. In addition, the structure functions support the detection of turbulent atmospheric conditions with signatures of flow anisotropy generated by enhanced thermal stratification in the UTLS. The scales involved are between the buoyancy length scale L B  ≈ 1, 500 m and the Ozmidov scale L O  ≈ 111 m. Plain Language Summary: This case study documents an aircraft encounter with clear air turbulence (CAT) that occurred over the remote Drake Passage. Exceptional atmospheric conditions are known to exist there as low‐pressure systems regularly pass through the passage. During a research flight conducted as part of the Southern Hemisphere Transport, Dynamics, and Chemistry campaign in November 2019, moderate to severe turbulence was detected using flight‐level observations of wind and temperature with a frequency of 10 Hz. The vertical distribution of atmospheric variables is provided by a high‐resolution radiosonde profile launched from the Argentinian research station Marambio. In addition, the results of global and regional numerical weather prediction models are used to provide the meteorological context and to derive indices commonly used to predict CAT for aviation. Two different analysis techniques are used to quantify the eddy dissipation rates associated with the CAT event. Both methods show that the event exhibits the characteristic feature of the bursty and intermittent nature of turbulence in the upper troposphere and lower stratosphere. Flow anisotropy is large outside the mixing regions of the CAT patch. Key Points: oderate to severe clear air turbulence (CAT) over the Drake Passage is analyzed from unique 10 Hz flight level in situ observations during a research flight as part of the Southern Hemisphere Transport, Dynamics, and Chemistry campaign in 2019 The main source of the turbulence is the enhanced flow deformation and shear in the vicinity of a tropopause fold generated by an eastward propagating polar low Both spectral as well as structure function methods are applied to quantify the eddy‐dissipation rates, the intermittency, and the flow anisotropy during the CAT event